FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Purwoto, Atharina Firjani Danish (Diponegoro Journal of Accounting, 2024)
Continuous earnings management can reduce the credibility and transparency of the company's financial reports, this can disrupt investor confidence in the company. This study was aimed to examine the effect of profitability, leverage, firm sixe, corporate governance, and audit quality on earnings management. The data used in this research are secondary data obtained from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022, 316 observation data. The sample selection uses purposive sampling technique and the analysis method is multiple linear regression.The research hypotheses are as follows: (1) profitability has a positive effect on earnings management, (2) leverage has a negatif effect on earnings management, (3) firm size has a negatif effect on earnings management, (4) corporate governance has a positive effect on earnings management, and (5) audit quality has a negatif effect on earnings management. The results show that profitability have a positif effect on earnings management and firm size have a negatif effect on earnings management. While leverage, corporate governance, and audit quality have no effect on earnings management.